Ozonesonde Quality Assurance: The JOSIE–SHADOZ (2017) Experience - Thompson, Anne M. (2019)
The ozonesonde is a small balloon-borne instrument that is attached to a standard radiosonde to measure profiles of ozone from the surface to 35 km with ∼100-m vertical resolution. Ozonesonde data constitute a mainstay of satellite calibration and are used for climatologies and analysis of trends, especially in the lower stratosphere where satellites are most uncertain. The electrochemical concentration cell (ECC) ozonesonde has been deployed at ∼100 stations worldwide since the 1960s, with changes over time in manufacture and procedures, including details of the cell chemical solution and data processing. As a consequence, there are biases among different stations and discontinuities in profile time series from individual site records. For 22 years the Jülich (Germany) Ozonesonde Intercomparison Experiment (JOSIE) has periodically tested ozonesondes in a simulation chamber designated the World Calibration Centre for Ozonesondes (WCCOS) by WMO. During October–November 2017 a JOSIE campaign evaluated the sondes and procedures used in Southern Hemisphere Additional Ozonesondes (SHADOZ), a 14-station sonde network operating in the tropics and subtropics. A distinctive feature of the 2017 JOSIE was that the tests were conducted by operators from eight SHADOZ stations. Experimental protocols for the SHADOZ sonde configurations, which represent most of those in use today, are described, along with preliminary results. SHADOZ stations that follow WMO-recommended protocols record total ozone within 3% of the JOSIE reference instrument. These results and prior JOSIEs demonstrate that regular testing is essential to maintain best practices in ozonesonde operations and to ensure high-quality data for the satellite and ozone assessment communities.